Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1038/sj.ejcn.1602470
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Iraqi mothers' socioeconomic status on their milk-lipid content

Abstract: Objective: To investigate the lipid content and fatty acid (FA) composition, especially n 3 long-chain polyunsaturated fatty acids (n 3 LCPUFAs) of mature breast-milk of Iraqi mothers and their relation to the socioeconomic status of the mothers. Design: A collection of mature breast-milk of mothers with three different socioeconomic status (lactation period 571 month). Setting: Mosul province (in the north of Iraq). Subjects: Mature breast-milk samples were obtained from a group of 20-to 35-year-old mothers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
2
15
1
Order By: Relevance
“…Bangladesh is also a high fish‐consuming nation, but the urban cohort we studied may have had more limited dietary choice because of economic or urban slum constraints. An earlier study among mothers of older infants in northern rural Bangladesh and another study among Iraqi mothers of different socioeconomic status noted a low intake of foods rich in PUFA among low‐income families (Al‐Tamer & Mahmood, 2006; Yakes et al, 2011), and this could explain the observed decreasing trend in SFA/PUFA with prosperity we also found.…”
Section: Discussionsupporting
confidence: 67%
“…Bangladesh is also a high fish‐consuming nation, but the urban cohort we studied may have had more limited dietary choice because of economic or urban slum constraints. An earlier study among mothers of older infants in northern rural Bangladesh and another study among Iraqi mothers of different socioeconomic status noted a low intake of foods rich in PUFA among low‐income families (Al‐Tamer & Mahmood, 2006; Yakes et al, 2011), and this could explain the observed decreasing trend in SFA/PUFA with prosperity we also found.…”
Section: Discussionsupporting
confidence: 67%
“…Socioeconomic factors, including family size, income and mothers education have, in an urban Iraqian population of mothers, been shown to influence n -3 FA concentrations in the BM [28]. We did not have such data in this small pilot study and also other confounding factors regarding maternal habits, like smoking was not registered, and are, together with the restricted dietary recording, the limitations of our study.…”
Section: Discussionmentioning
confidence: 86%
“…Other studies have reported regional and socio‐economic differences in lipid content of breast milk. Al‐Tamer and Mahmood found that lactating Iraqi women of lower socio‐economic status had altered lipid content and fatty acid composition of breast milk, especially the levels of n(3) long‐chain polyunsaturated fatty acids 20 . While Ruan et al .…”
Section: Discussionmentioning
confidence: 97%
“…Al-Tamer and Mahmood found that lactating Iraqi women of lower socioeconomic status had altered lipid content and fatty acid composition of breast milk, especially the levels of n(3) long-chain polyunsaturated fatty acids. 20 While Ruan et al reported in their study of milk composition from five different regions of China, that geography and maternal diet had a marked influence on milk fatty acid content. 14 We also found significant differences in the concentrations of protein and micronutrients (Mn, Fe, Cu, Na, K, Cl, P, Ca and Zn) in the breast milk of lactating mothers between Chongming and the three urban counties.…”
Section: Discussionmentioning
confidence: 98%